1445Antibiotic susceptibility of Helicobacter pylori in Arctic Canadian Indigenous communities. (2nd September 2021) - Lindsey, Lauren; Quilty, Doug; Cromarty, Taylor; Assi, Ali; Zanten, Sander Veldhuyzen van; Goodman, Karen
Abstract: Background: Our community-driven projects address concerns of Canadian Arctic Indigenous communities about Helicobacter pylori ( Hp ) infection, responsible for elevated gastric cancer mortality in the region. A key concern is poor effectiveness of anti- Hp treatment. We aimed to describe antibiotic resistance patterns in Hp isolated from project participants. Methods: Participants in 7 communities underwent upper gastrointestinal endoscopy with 2 gastric biopsies taken for tissue culture during 2008-2017. We tested Hp isolates for resistance to 7 antibiotics by Etest and assessed 4 outcomes: resistance to metronidazole, clarithromycin, 1+ antibiotics, and 2+ antibiotics. We tabulated proportion positive among isolates tested with 95% confidence intervals (CI) and used logistic regression to assess the relation of age and sex to resistance outcomes. Results: Of 259 Hp isolates tested, resistance to metronidazole, clarithromycin, 1+ antibiotics, and 2+ antibiotics were (% [CI]): respectively, 35 [29-41], 19 [15-25], 44 [38-50], and 12 [8-17] overall; 38 [30-47], 24 [17-32], 49 [41-58], and 16 [11-23] in 146 isolates from women; and 30 [22-39], 13 [8-21], 36 [27-46], and 6 [3-12] in 113 isolates from men. Odds of resistance to clarithromycin, 1+ antibiotics, 2+ antibiotics, and, to a lesser degree metronidazole, were elevated in women relative to men after age adjustment and increased with age in women but not men. Conclusion: In Arctic Indigenous communities in Canada, women were more likely than men to harbor antibiotic-resistant Hp, and their frequency of resistant Hp infection increased with age. Key messages: Community-driven research answers questions posed by those who bear the disease burden.